2016
DOI: 10.1038/ncomms10423
|View full text |Cite
|
Sign up to set email alerts
|

Membrane potential shapes regulation of dopamine transporter trafficking at the plasma membrane

Abstract: The dopaminergic system is essential for cognitive processes, including reward, attention and motor control. In addition to DA release and availability of synaptic DA receptors, timing and magnitude of DA neurotransmission depend on extracellular DA-level regulation by the dopamine transporter (DAT), the membrane expression and trafficking of which are highly dynamic. Data presented here from real-time TIRF (TIRFM) and confocal microscopy coupled with surface biotinylation and electrophysiology suggest that ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 56 publications
(71 citation statements)
references
References 70 publications
2
69
0
Order By: Relevance
“…An alternate possibility is that changes in DA neuron firing rate induced by HCRTr1 blockade in the absence of cocaine engenders adaptations in cocaine sensitivity at the terminal, as others have shown that changes in DA neuron excitability can affect DAT function (Richardson et al 2016). HCRTr1 blockade reduces DA neuron excitability, and thus it is possible that this effect could lead to changes in terminal calcium signaling that result in terminal DAT modifications that have been proposed to modulate DAT sensitivity to cocaine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An alternate possibility is that changes in DA neuron firing rate induced by HCRTr1 blockade in the absence of cocaine engenders adaptations in cocaine sensitivity at the terminal, as others have shown that changes in DA neuron excitability can affect DAT function (Richardson et al 2016). HCRTr1 blockade reduces DA neuron excitability, and thus it is possible that this effect could lead to changes in terminal calcium signaling that result in terminal DAT modifications that have been proposed to modulate DAT sensitivity to cocaine.…”
Section: Discussionmentioning
confidence: 99%
“…Potential mechanisms for altered DAT sensitivity to cocaine include differential DAT phosphorylation state (Moritz et al 2013), shifts in inward/outward facing DAT (Liang et al 2009), and changes in oligomer/monomer ratios (Chen and Reith 2007). DAT modification that is driven by changes in DA neuron excitability occurs within seconds of changes in DA neuron excitability (Richardson et al 2016), and thus we expect that this process could occur within the 30 min window that HCRTr1 blockade-induced reductions in terminal cocaine sensitivity have been observed. Ongoing experiments seek to test this possible explanation for altered terminal cocaine sensitivity following HCRTr1 blockade.…”
Section: Discussionmentioning
confidence: 99%
“…Adult male GT-tg bigenic mice, RFP::TH mice (Lin et al, 2016; Richardson et al, 2016; Saha et al, 2014; Sambo et al, 2017), and C57BL/6J wild-type (Jackson Labs, Bar Harbor, ME) mice (8–10 weeks of age) were maintained in the University of Florida animal facilities. All experiments were approved by the Institutional Animal Care and Use Committee.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to PKC, αCaMKII (Calmodulin-dependent Protein Kinase IIα) also plays a role in regulating amphetamine-induced dopamine efflux as its inhibition attenuates DAT-mediated dopamine efflux (Steinkellner et al, 2012). Because DAT transport is a sodium dependent transporter, sodium concentrations and membrane potential have also been shown to regulate uptake and efflux with more positive membrane potential—affected by sodium and calcium gradients—reducing uptake and favoring efflux (Khoshbouei et al, 2003; Khoshbouei et al, 2004; Gnegy et al, 2004; Richardson et al, 2016). Along the same lines, site-directed mutagenesis and functional studies have shown that N-terminal T62 is crucial for determining the favored DAT conformation, and that N-terminal phosphorylation is critical for amphetamine-induced efflux (Khoshbouei et al, 2004; Guptaroy et al, 2009; Guptaroy et al, 2011; Fraser et al, 2014), This indicates that these are sites of modification necessary for changing and stabilizing DAT conformation.…”
Section: Dat Regulation Of Dopamine Metabolism and Signalingmentioning
confidence: 99%